Penerapan Metode WASPAS dan ROC (Rank Order Centroid) dalam Pengangkatan Karyawan Kontrak - Fahrul Mahdi; Faisal; Dwina Pri Indini; Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The important determinant factor for the success of a service company in achieving its established objectives is its workforce. The selection process for new and contract employees in the company should be objective in order for them to become permanent employees. However, many companies still lack measures to evaluate the level of objectivity in their selection process. In this study, the author observed that sometimes companies experience difficulty in determining which contract employees should be promoted to permanent employees due to the lack of objectivity in the selection process. Therefore, the author used the Simple Additive Weighting (WASPAS and ROC) method to determine the best employees who can be promoted to permanent employees with criteria such as participation, level of education, competency, workplace, knowledge, teamwork, work quality, English language skills, and others. Based on the research results, the ROC and WASPAS methods are very useful in determining the best employee candidates and solving identified problems, as well as providing better and more optimal results in decision-making. In this study, variant A2 with the highest utility value of 0.982 was chosen as the best contract employee to be employed as a permanent employee.